New photocatalyst electrodes and their photocatalytic degradation properties of organics - Li, Xin Yong; Zhao, Q.; Quan, X. (2010)
This review describes recent development of photocatalysts and their performance in degrading organics. As the core of photocatalytic technique, photocatalysts with improved performance, high energy efficiency, environmental benignity, low cost and long lifetime are desirable. Favorable strategies to produce photocatalysts with high degradation efficiency are selectively compared. Some new film electrodes with advanced nano-architectures (nanowire, nanotube arrays, nanoporous, hierarchical structures, etc.), which can work under visible light and utilize more photo-induced charges assisted by electric bias, are discussed for their promising application in environmental purification. The effects of common factors, such as light intensity, pH value of solution, original concentration of organics, dissolved oxygen concentration, etc. on the photocatalytic degradation of some organic species are preferentially remarked. © 2010 Bentham Science Publishers Ltd.